Central venous catheter detachment with migration to the right atrium: A rare complication of a common implantable device - Jacob Van Vorst, DO; Michael Hollander, MD; Francis Flaherty, MD (Radiology Case Reports, 2025)
The intravascular embolization of catheter fragments is an uncommon yet potentially serious complication of central venous catheters (CVC). We present the case of an 81-year-old female with a history of endometrial cancer who presented from an oncologic appointment with a nonfunctioning chest port (CVC). The chest port was placed 10 months prior without complication. An initial fluoroscopic image of the chest revealed detachment and migration of the catheter towards the right atrium. The catheter was successfully retrieved with a gooseneck snare using an inferior approach through the femoral vein. Catheter detachment and embolization is a rare complication of CVCs that should be included in the differential of a nonfunctional port.